NILAI EKONOMI JASA LINGKUNGAN KAWASAN KARST GUA GUDAWANG - Joko Mijiarto; Sambas Basuni; Tutut Sunarminto (Media Konservasi, 2014)
The economic value of Gudawang Cave are still limestone product (goods) which gotten from mining activities and environtment product (service) that has been used as new area of tourism development. Other environmental services such as source of water and fauna habitat have not been used optimally and provide economic value to society yet. The research question is how is the utilization of Gudawang Cave area as economical-ecology can be optimal  and sustainable. It is necessary to determine of the economic value of environmental services as the basis for its management and utilization. The economic value of Cave Gudawang environmental services which was calculated in this study was the economic value of the Cave Gudawang as a source of water, as bat habitat (as pest control and fertilizer guano) based Market Based Approach; and tourism economic value by using the Individual Travel Cost Method approach. Result of the study showed that the economic value of Gudawang Cave karst area environmental services was Rp. 1.222.673.877,00/year. This value were from the value of benefits water Rp. 1.060.680.000,00, the value of bats as pest control was Rp. 10.800.000,00, economic value of  guano Rp. 2.403.744,00 and economic value of  tourism Rp. 148.790.133,00. Keywords: Economic valuation, Eeconomic value, Eenvironmental services, Gudawang Cave, Karst area